An Assessment of the Port of London as a Node for Critical Supplies in the United Kingdom - Breckenridge, Stephanie (2011)
Is the Port of London critical national infrastructure? All ports are considered important by the industries they serve but not all will be critical to the country in which they are located. The Port of London is the second largest United Kingdom (UK) port but that fact alone may not be enough for it to qualify (Department for Transport, 2010). The first step in answering the question is to define what should be considered critical national infrastructure. In the UK, the Centre for the Protection of National Infrastructure is a governmental agency that provides resources to national infrastructure that it considers to be critical. Its definition includes infrastructure which, if lost, would have a detrimental effect on the UK economy (Centre for the Protection of National Infrastructure 2, 2011). The data from the National Maritime Statistics reveals that the cargo passing through the Port of London is extremely diverse. One way of clarifying the role of the port is to focus on a single important supply. The Port of London is home to the worlds largest sugar refinery, providing 40.7% of the European Unions capacity for refining sugar cane (Bacon, 2011). The UK food, beverage and confectionery industry is dependent on the production of sugar with 75% of the sugar in the UK being sold to companies in that sector (Department for Environment, Food, and Rural Affairs, 2007). The Port of London is also the second largest of the 51 major UK ports. The single largest UK port is highly specialised for handling energy commodities and many of the others tend to specialise in other specific cargo categories (Department for Transport, 2010). The Port of London’s cargo is diverse, with the Tate & Lyle refinery being just one of the port’s terminals. The combination of the Port of London’s size and the presence within it of a large, capital-intense refinery would make it difficult for the other UK ports to replace its loss. Therefore I conclude that the Port of London should be considered critical national infrastructure.